Reformation in Italy in the 16th century - Hajnóczi, Kristóf (Church History Review, 2024)
The article is a brief summary of the emergence, spread, decline and disappearance of the ideas of Protestant Reformation in Italy in the 16th century. It reviews the related intellectual currents in Italy, points out the areas affected, traverses the period traced in the relevant Italian literature, presents figures, describes the most important groups and communities involved, and briefly describes the Bible translations, as well as the two most important works associated with the Protestant Reformation in Italy.
Keywords: Array; Array; Array; Array